Effect of Hypertension Self Management Education (HSME) Against Patients' Blood Pressure Hypertension During the Covid-19 Pandemic - Mareta Dea Rosaline; Fiora Ladesvita; Lima Florensia; Sondang Mariani (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
In preventing the spread of COVID-19 transmission, it is deemed necessary to strengthen the prevention of COVID-19 transmission in people with vulnerable groups and COVID-19 comorbidities. Hypertension is a non-communicable disease of concern during the COVID-19 pandemic. Education plays an essential role in efforts to improve blood pressure control for the application of behavior during the COVID-19 pandemic in hypertensive patients. This study aimed to determine the effect of Hypertension Self Management Education (HSME) on blood pressure of hypertensive patients during the COVID pandemic. The research method is a quasi-experimental method using pre-test and post-test with control group design. The research sample consisted of 42 respondents divided into 22 intervention groups and 22 control groups. The results showed that there was an effect of Hypertension Self Management Education (HSME) on systolic and diastolic blood pressure (p = 0.00 < 0.05). Thus, there is an effect of HSME on blood pressure in hypertensive patients at Posbindu Dahlia Senja, Depok. Therefore, nurses are advised to provide HSME health education to control the blood pressure of hypertensive patients and utilize HSME as a health promotion program. Keywords: Hypertension, Hypertension Self Management Education, Blood Pressure.